Research on the Opportunity Identification and Pattern Innovation of Artificial Intelligence Technology in the Development of Silver Economic Market in Young Entrepreneurs - Gan, Xinhang (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
With the increasing aging of the global population, the silver economic market contains great potential. The rapid development of artificial intelligence technology has brought unprecedented opportunities for young entrepreneurs to explore the silver economic market. This paper deeply analyzes the application status of artificial intelligence technology in the silver economic market, and identifies opportunities for young entrepreneurs in this process, including meeting the diversified needs of the elderly, improving service efficiency and quality, and tapping new business value. At the same time, the paper discusses the innovation of entrepreneurship models based on artificial intelligence technology, such as intelligent health care service model, personalized elderly product customization model, intelligent elderly social and entertainment model, and puts forward corresponding development strategies and suggestions, aiming at providing theoretical basis and practical guidance for young entrepreneurs to successfully start their own businesses in the field of silver economy.